Assessing climate literacy in secondary schools: development and validation of an interdisciplinary competence test - Martin, Monika; Stadler, Magdalena; Künsting, Josef; Schwichow, Martin; Asshoff, Roman; Bender, Ute; Birke, Franziska; Carrapatoso, Astrid; Grundmeier, Anne-Marie; Höger, Christian; Schuler, Stephan; Stemmann, Jennifer; et al. (Frontiers in Education, 2025)
IntroductionA key goal of Climate Change Education (CCE) in schools is promoting climate literacy in students, that is, equipping them with the skills needed to engage in climate-related discourse and actions in an informed way. To determine whether CCE achieves this goal, comprehensive assessment is essential. However, existing assessment instruments focus narrowly on factual scientific knowledge of climate change and offer limited insight into students' broader climate literacy. This study presents the development of an interdisciplinary climate literacy test for secondary students, integrating perspectives from nine school subjects across the natural sciences, social sciences, technology, and the humanities.MethodThe development process involved a cognitive pretest (N = 20), two pilot studies (N1 = 353, N2 = 313), a teacher survey (N = 36), and a validation study (N = 825). We provide a validity argument supporting interpretation of the test score as a meaningful measure of CCE outcomes in secondary education.ResultsThe test difficulty is suited for 9th-grade students (approximately 15 years old) across all school types in Germany. Empirical results support the theoretically derived four-dimensional structure of climate literacy, covering the four competence facets of (1) Dealing with content knowledge, (2) Knowledge generation and evaluation, (3) Information and communication, and (4) Normative evaluation. Correlations with external variables suggest that the test captures a school-related competence that is relevant to students' everyday lives.DiscussionThe developed test provides an interdisciplinary and detailed assessment of secondary students' climate literacy. We recommend its use for comprehensive evaluation of CCE efforts, enabling the design of more targeted and effective interventions.